Comparison of personal independence between soft dressing and immediate postoperative prosthesis method in older diabetic amputees - seyed mahmoud mousavi ziarati; kia hedayatrad; aliakbar nazari; mohammad reza kalantar motamed; behnoush asadollahi dehkordi (Journal of Rehabilitation Sciences and Research, 2021)
Background: Elderly diabetic patients face a lack of independence in daily and social activities such as going to the toilet and bathing, aside from walking and communication, which are affected by the ability to stand and walk bilaterally. This study aims to compare the rehabilitative outcome of post-amputation soft dressing with IPOp Method and materials: In this randomized clinical trial study four parameters were measured, including the time between amputation and the first standing, amputation and taking the first steps, amputation and an independent personal activity and amputation and fitting the first permanent prosthesis. Thirty elderly diabetic patients (aged 65-80) were divided into two groups. The Intervention group received IPOP and the control group received soft dressing. results: Patients who received immediate post-operative prosthesis took significantly lower time in all four variables. Conclusion: The results showed that it takes the control group, on average, 148 days longer to receive their first final prosthesis and achieve the same ADL and social status as the intervention group.